Boneca de Atauro: Searching for the Lost Love - Palazón, David (East Timor, 2016)
The film is the first stop-motion film coming out the young nation of Timor-Leste. The main character is a handmade rag doll looking for her abducted partner, takes us into an adventurous journey through some of the locations in Ataúro island .
The film dialogues are in Tetun.